Hubungan Pola Asuh Orang Tua dengan Interaksi Sosial pada Teman Sebaya pada Siswa Kelas Va di SDN 1 Bukit Tunggal Palangka Raya - Erna Erviana; Dwi Agustian Faruk Ibrahim; Ayu Puspita (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Parenting plays a significant role in shaping a child's personality. The issue of parenting arises due to the lack of parental attention towards their children, often because parents are preoccupied with work. This phenomenon is observed at SD Negeri 1 Bukit Tunggal in Palangka Raya, where there is a lack of social interaction among peers, as seen from children's behavior, such as preferring to be alone, having poor communication with peers, and lacking empathy, which results in low sensitivity to their social environment. This study aims to examine the relationship between parenting styles and peer social interaction among Grade VA students. Method: The research design used was a correlation study with a cross-sectional method, aimed at identifying the correlational relationship between two variables. The instruments used in this study were questionnaires and the Spearman Rank statistical test, administered to 36 students in Grade VA. Results: The significance value of the relationship between parenting styles and social interaction at SDN 1 Bukit Tunggal was 0.548 > 0.05. Therefore, the hypothesis H1 was rejected, indicating that there is no relationship between parenting styles and peer social interaction among Grade VA students at SDN 1 Bukit Tunggal, Palangka Raya. Conclusion: There is no relationship between parenting styles and peer interaction in the process of shaping children's personalities, based on the research results.